The SASP factor IL ‐6 sustains cell‐autonomous senescent cells via a cGAS ‐ STING ‐ NFκB intracrine senescent noncanonical pathway - Herbstein, Florencia Lucía (2024)
Senescent cells produce a Senescence-Associated Secretory Phenotype (SASP) that involves factors with diverse and sometimes contradictory activities. One key SASP factor, interleukin-6 (IL-6), has the potential to amplify cellular senescence in the SASP-producing cells in an autocrine action, while simultaneously inducing proliferation in the neighboring cells. The underlying mechanisms for the contrasting actions remain unclear. We found that the senescence action does not involve IL-6 secretion nor the interaction with the receptor expressed in the membrane but is amplified through an intracrine mechanism. IL-6 sustains intracrine senescence interacting with the intracellular IL-6 receptor located in anterograde traffic specialized structures, with cytosolic DNA, cGAS-STING, and NFκB activation. This pathway triggered by intracellular IL-6 significantly contributes to cell-autonomous induction of senescence and impacts in tumor growth control. Inactivation of IL-6 in somatotrophic senescent cells transforms them into strongly tumorigenic in NOD/SCID mice, while re-expression of IL-6 restores senescence control of tumor growth. The intracrine senescent IL-6 pathway is further evidenced in three human cellular models of therapy-induced senescence. The compartmentalization of the intracellular signaling, in contrast to the paracrine tumorigenic action, provides a pathway for IL-6 to sustain cell-autonomous senescent cells, driving the SASP, and opens new avenues for clinical consideration to senescence-based therapies.